Teacher's Strategy in Formation of Islamic Character for Grade 10 Students of Madrasah Aliyah: Strategi Guru Dalam Pembentukan Karakter Islami Siswa Kelas 10 Madrasah Aliyah - Aqidatul Nur Idzha; Isa Anshori (Academia Open, 2021)
The purpose of this study was to explore and understand the strategies of Islamic Religious Education teachers in shaping the Islamic character of the 10th grade students of MA Ma'arif Durensewu, Pasuruan Regency, the supporting and inhibiting factors in the formation of the Islamic character of the 10th graders of MA Ma'arif Durensewu, Pasuruan Regency, and solutions. and problem solving taken by the teacher in shaping the Islamic character of the 10th grade students of MA Ma'Arif Durensewu, Pasuruan Regency. To achieve this goal, the researchers used qualitative research methods with a phenomenological approach. The research subjects were PAI teachers, 13 female students, and 11 male students. The types of data collected are qualitative and quantitative, primary sources and secondary sources. Meanwhile, for data collection, the researcher used observation, interview, and documentation techniques. The data obtained were analyzed through reduction, display and draw conclusions. The results showed that the strategy of Islamic Religious Education teachers in shaping students' characters used cooperative learning, Problem Based Learning, and Project Based Learning models. Supporting factors in shaping the character of students are the religious atmosphere created by the madrasa that is very good, for example, providing an assessment of congregational prayers, students are required to take religious extracurricular activities, the field of Islamic Da'wah and Islamic Music, etc. The inhibiting factor is the very varied parental background and the less supportive community environment. The solution provided by Islamic Religious Education teachers in solving these problems. Keywords: Learning Strategies, PAI teachers, Islamic Character Building.